Community Competition Is the Microorganism Feedback to Sedimentary Carbon Degradation Process in Aquaculture Tidal Flats - Zhou, Min; Fang, Fu-Tao; Zeng, Cong; Zhang, Li-Hong; Zhou, Cheng-Xu; Zhu, Zhuo-Yi (Frontiers in Marine Science, 2022)
How the microbial community response to carbon degradation is unclear, while it plays an essential role in predicting microbial community shift and determining carbon cycling. Surface sediments in two contrasting aquacultural tidal flat sites in Fujian Province, China, were collected in October, 2020. In addition to 16s rRNA gene high-throughput sequencing for determining bacteria and archaea biodiversity, an amino acids-based molecular degradation index DI was used to quantify the carbon degradation status. The results revealed that the microorganism response to DI at the family level was community competition. Specifically, the winning microbes that grew under carbon degradation (i.e., operational taxa unit numbers negatively related with the degradation index) accounted for only 18% of the total family number, but accounted for 54% of the total operational taxa unit numbers. Network analysis confirmed the oppressive relation between winners and the rest (losers + centrists), and further suggested the losers survival strategy as uniting the centrists. These findings shed new light on microorganism feedback to carbon degradation, and provide a scientific basis for the explanation of microbial community shift under progressive carbon degradation.